Pengaruh Rasio Keuangan Terhadap Harga Saham Sektor Perbankan Selama Pandemi Covid-19 2019-2021 - Simanjuntak, Joshua (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of financial ratios on stock prices. The ratios used are NPM, DER, CR, ROA and TATO. The population of this study are all banking companies listed on the Indonesia Stock Exchange (IDX) in 2029-2021 which year is the beginning and peak of the Covid-19 pandemic. The sampling technique uses purposive sampling. Data analysis technique using panel data regression with e-views application 10. The population of this study amounted to 47 companies and the samples obtained were 37 companies. Observations made by researchers on 141 company years. This study proves, first, that the NPM variable is supported or the results show negative. Second, the DER variable has a negative effect on stock prices. Third, the CR variable is not supported. Fourth, the ROA variable in the fourth hypothesis must be discarded because all the assumptions needed in the first data processing are not supported, so data transformation is needed. Fifth, the TATO variable affects stock prices. Kata kunci: NPM, DER, CR, ROA, TATO, Harga Saham. The purpose of this study is to obtain empirical evidence regarding the effect of financial ratios on stock prices. The ratios used are NPM, DER, CR, ROA and TATO. The population of this study are all banking companies listed on the Indonesia Stock Exchange (IDX) in 2029-2021 which year is the beginning and peak of the Covid-19 pandemic. The sampling technique uses purposive sampling. Data analysis technique using panel data regression with e-views application 10. Observations made by researchers on 141 company years. This study proves, first, the NPM variable in the first hypothesis is not supported or the results show negative. Second, the DER variable in the second hypothesis is supported, namely DER has a negative effect on stock prices. Third, the CR variable in the third hypothesis is not supported. Fourth, the ROA variable in the fourth hypothesis must be discarded because all the assumptions needed in the first data processing are not supported (figure 11) so that data transformation is needed. Keywords: NPM, DER, CR, ROA, TATO, Stock Price.